(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Digital monitoring has become a key instrument in modern customs administration, significantly transforming the management of goods movement under the customs processing regime. This study examines the role of digital technologies in ensuring efficient control, transparency, and optimization of goods flow within customs territories. The research highlights how tools such as electronic declaration systems, real-time tracking, risk management platforms, and automation contribute to reducing transaction costs, minimizing human errors, and accelerating customs procedures. The study also evaluates the efficiency of digital monitoring through key performance indicators, including processing time, administrative costs, compliance level, and operational transparency. The findings suggest that digital monitoring enhances both macroeconomic outcomes, such as trade facilitation and export growth, and microeconomic performance, including enterprise efficiency and cost reduction. Overall, the integration of digital monitoring systems is identified as a critical factor in improving the effectiveness of the customs processing regime and strengthening its role in global trade facilitation.